PENGGUNAAN TEKNIK ROTOSCOPING DAN MOTION TRACKING 3D DALAM PEMBUATAN VIDEO COMPOSITION - purwanto, Agus; Suyanto, M.; Luthfi, Emha Taufiq (Universitas Respati Yogyakarta, 2013)
World Visual effects or CGI (Computer Graphic Imagery) has been applied in various forms such as TV commercial video presentations and movies. Basically the CGI technique is a technique combining two or more video and animation so that it becomes a single unit video harmonious composition. Basic techniques used in combining the elements - the constituent elements are keying rotoscoping and motion tracking. Keying and rortoscoping used to select part of an image and motion tracking is used to detect the motion of a point marker on a video. This study discusses how to apply motion tracking and rotoscoping techniques 3D, in making a video composition.Â Keyword : Motion tracking 3D, rotoscoping, visual effect, video compositing.